2003
DOI: 10.1021/ie020833t
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Selection of Controlled Variables

Abstract: This paper considers the selection of controlled variables for the unconstrained degrees of freedom, such that near-optimal operation is achieved with constant setpoints ("self-optimizing control"). From a second-order Taylor approximation around the optimal point, we derive an exact local method. This may be used to find the optimal linear combination of measurements to use as controlled variables. We also derive the approximate singular value rule, which is very useful for quick screening and elimination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
286
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(288 citation statements)
references
References 6 publications
0
286
0
2
Order By: Relevance
“…A preliminary screening was performed by using the maximum scaled gain method (Halvorsen et al, 2003). Some variables where discarded based on these results (e.g.…”
Section: Selection Of Controlled Variablesmentioning
confidence: 99%
“…A preliminary screening was performed by using the maximum scaled gain method (Halvorsen et al, 2003). Some variables where discarded based on these results (e.g.…”
Section: Selection Of Controlled Variablesmentioning
confidence: 99%
“…A detailed derivation of the minimum singular value is given in Halvorsen, Skogestad, Morud, & Alstad ( 2003). It is shown that for small disturbances (local behavior) and with the scaling mentioned above, the expected worst-case loss is bounded by…”
Section: Minimum Singular Value Rulementioning
confidence: 99%
“…It is possible to find the locally optimal linear measurement combination H as proposed by Halvorsen et al (2003). The local-behavior assumption makes it possible to use the maximum singular value of a matrix M to effectively evaluate the loss for all expected disturbances and implementations error.…”
Section: Without Implementation Errormentioning
confidence: 99%
See 2 more Smart Citations